2018
DOI: 10.1021/acsaem.8b01274
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of High Densities of Antisite Defects in Ag2ZnSnSe4

Abstract: The limited efficiency of Cu 2 ZnSn(SSe) 4 (CZTSSe) solar cells has been widely attributed to band tailing due to high densities of Cu Zn and Zn Cu antisite defects. It has been proposed that the partial replacement of Cu by Ag should reduce the antisite defect density, leading to reduced band tailing and increased cell efficiencies. This article examines antisite defects in Ag 2 ZnSnSe 4 (AZTSe) crystals grown at high temperatures from a stoichiometric mixture of elements by scanning transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…This additional absorption edge is not related to any of the possible secondary phases (i.e., AgSe, Ag 2 Se, ZnSe, SnSe, SnSe 2 , AgSnSe 2 , Ag 8 SnSe 6 , and Ag 2 SnSe 3 ) as per the reported bandgap values data in literature . Cherns et al also observed such an additional band edge for stoichiometric AZTSe crystal, and they claim that it is associated with Ag Zn defect complex . The theoretical study predicts the lowest formation energy for Ag Zn defect complex in Zn‐poor/stoichiometric samples .…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…This additional absorption edge is not related to any of the possible secondary phases (i.e., AgSe, Ag 2 Se, ZnSe, SnSe, SnSe 2 , AgSnSe 2 , Ag 8 SnSe 6 , and Ag 2 SnSe 3 ) as per the reported bandgap values data in literature . Cherns et al also observed such an additional band edge for stoichiometric AZTSe crystal, and they claim that it is associated with Ag Zn defect complex . The theoretical study predicts the lowest formation energy for Ag Zn defect complex in Zn‐poor/stoichiometric samples .…”
Section: Resultssupporting
confidence: 52%
“…Furthermore, selenized AZTSe films ( T Se ≤ 400 °C) show an additional absorption edge at the lower energy side (S6, Supporting Information). This additional absorption edge is not related to any of the possible secondary phases (i.e., AgSe, Ag 2 Se, ZnSe, SnSe, SnSe 2 , AgSnSe 2 , Ag 8 SnSe 6 , and Ag 2 SnSe 3 ) as per the reported bandgap values data in literature . Cherns et al also observed such an additional band edge for stoichiometric AZTSe crystal, and they claim that it is associated with Ag Zn defect complex .…”
Section: Resultssupporting
confidence: 52%
“…Additionally, the same authors hypothesized that Ag Cu could form deep acceptor trap states, thus reducing the concentration of Cu vacancies and most probably with an effect on the carrier's concentration level. In contrast, the opposite effect has been reported, where Cherns et al observed a high level of disorder (large amount of Cu and Ag antisites) in Ag containing crystals . The effect of Ag in the reduction of disorder on kesterite is still debatable, although we must consider that it could be strongly related to the thermal history of the sample .…”
Section: Challenges and Perspectives: How To Improve The Kesterite Efmentioning
confidence: 76%
“…A theoretical study presented by Yuan et al highlighted the potential of Cu substitution by Ag, predicting that Ag‐based kesterite must exhibit either intrinsic or weak n‐type conductivity due to the very low concentration of Ag Zn antisite defects, in addition to the fact that the dominant defects are donors, most probably Zn Ag . They proposed that alloying of Cu 2 ZnSn(S,Se) 4 with Ag can be helpful to overcome the V OC deficit due to a reduction in defect concentration, a conclusion which was further supported by Chagarov et al, but later contradicted by the work of Cherns et al Nevertheless, and as was highlighted before, the disorder also strongly depends on the thermal history and composition of the samples, so deeper and complementary studies are required to validate all these results. Additionally, composition‐graded (Cu,Ag) 2 ZnSn(S,Se) 4 alloys provide interesting perspectives in band engineering for boosting the efficiency of kesterite.…”
Section: Challenges and Perspectives: How To Improve The Kesterite Efmentioning
confidence: 90%
“…This strategy was theoretically proposed as an effective method to reduce the concentration of Cu Zn antisite pairs [63,64]. The substantially higher crystal radius of Ag + (1.14 Å) compared to Cu + (0.74 Å) contributes to the higher formation energy of antisite defects and Ag-related defect complexes such as Ag Zn +Zn Ag and 2Ag Sn +Sn Zn in Ag 2 ZnSnS 4 (AZTS) based on theoretical calculations [18,[65][66][67] (figure 9(a)). The lower valence band edge in AZTS (by 0.74 eV) also plays an important role in decreasing the amount of antisite defects [65].…”
Section: Silver (Ag)mentioning
confidence: 99%